Assessment of the Attitude of Youth towards Entrepreneurship: Evidence from Surkhet Nepal - Rana , Mahesh; Subedi, Arun; Dhakal, Amrit; Shrestha, Samrat (Kalika Journal of Multidisciplinary Research, 2024)
The growth of entrepreneurial spirit is crucial for economic progress, which is why this topic of study has attracted significant attention recently. The knowledge youths acquire in entrepreneurship has a substantial influence on their impressions of this field. This study aims to assess youth’s attitudes towards entrepreneurship. Furthermore, this study seeks to examine the influence of social networks, access to capital, education, government assistance policies, and creativity and risk-taking on the attitudes of young entrepreneurs. A descriptive and causal-comparative research design were employed in this study. A convenience sample was used to choose 150 young entrepreneurs (aged 20 to 35) from the Surkhet District. Data collection was conducted using a self-administered questionnaire. The IBM SPSS 26 software was utilized to conduct both descriptive and inferential analyses. The findings revealed that dimensions of the entrepreneurial attitude of youth including social networks, access to capital, education, government support policy, and creativity and risk-taking had positive and significant impacts on entrepreneurial attitude. The study has significant implications for economic development, community participation, education, support systems, and policy, all of which are crucial for building a dynamic entrepreneurial ecosystem among the young of Surkhet, Nepal.